IMPLEMENTASI ALGORITMA FUZZY EVOLUSI UNTUK PENGATURAN JADWAL LABORATORIUM KOMPUTER DI SEKOLAH - Luqman Abdul Malik; Elkaf Rahmawan Pramudya (Universitas Raharja, 2017)
Problems in the placement of the clock and the use of the computer lab this time wearing schedule which already available, but the use of spaces and their subjects will use laboratory space is not yet available on the schedule of lessons. This is a constraint in the use of computer lab room each day and happens constantly every day and every week. But yet the formation schedule use of a computer lab space evenly for classes which does require a competence in practice the subjects and rely solely on coming first entered in the computer lab. Scheduling the use of the computer lab is expected to obtain a schedule by the number of hours of instruction that are already defined and a timetable of the lessons taught are evenly distributed to every teacher lessons and students can be met to use the computer lab right on schedule in order not to occur collisions. In the fuzzy algorithm of evolution has several stages, among others: Represent chromosome, Initialize the population, Determining the function of Evaluation, doing the selection, Specify the Operator and include a combination of genetics, in the crossover and mutation.